Reflective Teaching for Undergraduate Courses:An Experience - Siddamal, Saroja V.; Budihal, Suneeta V.; Patil, Ujwala B. (Journal of Engineering Education Transformations, 2025)
The paper presents a reflective approach for the undergraduate's courses to improve the effectiveness of teaching. The objective of the proposed practice is to enhance the course learning, beyond the traditional mode. In the traditional method of teaching the course instructor would not have checked the effectiveness of the teaching till the completion of the course. The student also would not have measured the level of understanding. This creates a gap between teaching and learning. The reflective teaching breaks this vicious circle and promotes better teaching and learning. To meet the objective different activities such as cyclic test and concept visualization are designed and practiced in the identified courses. The proposed approach provides opportunities to refine course delivery and improve learning.